2013
DOI: 10.3329/jbau.v10i2.14917
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementation of fish meal on growth and reproductive performance of crossbred heifers

Abstract: The experiment was conducted at Bangladesh Agricultural University Dairy Farm to study the effect of fish meal (FM) on growth and reproductive performances of crossbred heifers. The experiment was designed into four treatment (T 0 =0% FM; T 1 =5% FM; T 2 =7.5% FM and T 3 =10% FM) groups having initial weight 231. 33 ± 32.39, 241.00 ± 46.29, 198.66 ±58.53 and 236.66 ± 31.64 kg, respectively. The average age of the animal is 2 years 9 month.Results of the experiment revealed that there was a significant differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Similarly Rocha et al, (1995) reported that group of Brahman bulls fed with fish meal had significantly higher average daily gain as compared to control group. Alam et al, (2012), Ortigues et al, (1990) and Calzadilla et al, (1992) observed that daily weight gain of heifers was significantly higher when basal diet was supplemented with fish meal. Gajera et al, (2013) in the group of Jaffrabadi buffalo heifers and Sai et al, (2014) in the group of crossbred calves, reported higher daily weight gain in treatment group supplemented with bypass Methionine and Lysine in the ration over that of control group.…”
Section: Average Daily Gain (Adg)mentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly Rocha et al, (1995) reported that group of Brahman bulls fed with fish meal had significantly higher average daily gain as compared to control group. Alam et al, (2012), Ortigues et al, (1990) and Calzadilla et al, (1992) observed that daily weight gain of heifers was significantly higher when basal diet was supplemented with fish meal. Gajera et al, (2013) in the group of Jaffrabadi buffalo heifers and Sai et al, (2014) in the group of crossbred calves, reported higher daily weight gain in treatment group supplemented with bypass Methionine and Lysine in the ration over that of control group.…”
Section: Average Daily Gain (Adg)mentioning
confidence: 97%
“…Unfortunately, in many part of India farmers considers buffalo heifer to be unproductive and hence they do not feed them properly. How a heifer develops into her potential for milk production depends upon how well we raise and manage her (Alam et al, 2012). Nutrition draws the greatest attention because lack of proper nutrition can reduce the reproductive efficiency.…”
Section: Issn: 2319-7706 Volume 7 Number 03 (2018)mentioning
confidence: 99%
“…Also, MOC is rich in lysine and sulphur containing amino acids (Klockeman, 1997). It has been scientifically proved that addition of fish meal in the concentrate mixture improve the reproductive performance of heifer (Alam et al, 2012). Monitoring of nutritional status of the animal are vital because these are the indicators of health status (Ate et al, 2009); and used for measuring energy and protein status.…”
Section: Introductionmentioning
confidence: 99%